Asia's ‘Boom’ of Difficult Memories: Remembering World War Two Across East and Southeast Asia - Schumacher, Daniel (History compass, 2015)
This article takes a cue from the tremendous increase in the creation of public sites of memory in Asia over the last few decades that are dedicated to the devastating events that took place in the Asian theatre of World War Two. The dissonant representations of these events still evoke strong emotions in the region and reveal many unresolved conflicts that stem from this war. This paper will survey the current research on the public remembrance of the Second World War in East and Southeast Asia. It will first delineate the most critical turning points in publicly recalling and framing the war by examining Asia's selective ‘memory boom’ in the 1980s and 1990s and the spread of victimhood narratives across the region. It will go on to assess the repercussions of these processes for reconciliation efforts that seek to tackle and resolve the quarrels fought over differing representations of the war in Asia - a topic, which has begun to attract considerable scholarly attention. The conclusion will suggest that furthering research on non-state actors, transnational forces, and on local religious characteristics in the processes of memory-making might help us to arrive at a more nuanced understanding of what has been labelled Asia's ‘Memory Problem’ and perhaps even forge new routes to reconciliation.